THE EFFECT OF BLADE CURVATURE ANGLE OF SAVONIUS WIND TURBINE L-TYPE ON THE PERFORMANCE - Barlin Barlin; Chandra Octavian Pratama; Krerkiat Sasiwimonrit (Indonesian Journal of Engineering and Science (IJES), 2021)
The wind is a renewable energy source (alternative energy) as a substitute for the dwindling fossil fuel. L-type Savonius wind turbine is a technology that is widely used to convert wind energy into mechanical because its construction is simple and cheap. The disadvantage of this turbine is having a lower efficiency than other types of wind turbines. Modification of the curvature of the L-type Savonius wind turbine blade is assumed can improve its performance because it affects the direction and magnitude of wind and wheel velocity, consequence impact to power. Thus, the blade angle is interesting to review. There are three angles of blade studied: 30º, 45º, and 60º. Based on results, the blade angle influences the performance of the L-type Savonius wind turbine, where the 45º blade angle produced better performance than 30º and 60º.